2011
DOI: 10.1037/a0022406
|View full text |Cite
|
Sign up to set email alerts
|

The structure of musical preferences: A five-factor model.

Abstract: Music is a cross-cultural universal, a ubiquitous activity found in every known human culture. Individuals demonstrate manifestly different preferences in music, and yet relatively little is known about the underlying structure of those preferences. Here, we introduce a model of musical preferences based on listeners’ affective reactions to excerpts of music from a wide variety of musical genres. The findings from three independent studies converged to suggest that there exists a latent five-factor structure u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
341
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(397 citation statements)
references
References 53 publications
22
341
1
12
Order By: Relevance
“…No participant reported any serious hearing impairment. Each participant chose two preferred musical genres as an open question-from these responses it was observed that the participants had diverse preferences, as the categories proposed by [28] were represented (mellow, unpretentious, sophisticated, intense, and contemporary). The overall test duration varied by participant, with median duration of 38 minutes, ranging from 22 to 69 minutes.…”
Section: Test Panelmentioning
confidence: 99%
“…No participant reported any serious hearing impairment. Each participant chose two preferred musical genres as an open question-from these responses it was observed that the participants had diverse preferences, as the categories proposed by [28] were represented (mellow, unpretentious, sophisticated, intense, and contemporary). The overall test duration varied by participant, with median duration of 38 minutes, ranging from 22 to 69 minutes.…”
Section: Test Panelmentioning
confidence: 99%
“…Many people seek out music for their own listening purposes, and, taken together with background music, this can add up to more than a quarter of a Western individual's day; especially adolescents (Rentfrow, Goldberg, & Levitin, 2011;Huron, 2001;Levitin, 2006;McCormick, 2009;Roberts, Henriksen, & Foehr, 2004). The importance of music is also reflected in the billions of dollars spent each year on: (a) music's consumption, and (b) music's construction by industry (Geter & Streisand, 1995).…”
Section: Why Investigate Music Preferences?mentioning
confidence: 99%
“…their music preference) has received relatively little attention in mainstream social, and developmental psychology, recent investigations have begun to examine individual differences in music preferences (for a review, see Rentfrow, McDonald, & Oldmeadow, 2009). However, additional research that validates music preferences as a measure of developmental accomplishments and issues is needed (Rentfrow, Goldberg, & Levitin, 2011). Exposing individuals to a specific variety or genre of music may promote greater self-exploration, validation, and normalization of their psychosocial, psychological, and developmental issues, thus enhancing their social development (Schwartz & Fouts, 2003).…”
Section: Why Investigate Music Preferences?mentioning
confidence: 99%
“…And just as musical preferences appear to be, in part, manifestations of personality traits and values, it is reasonable to expect that given the emotionally communicative nature of music, people's preferences may be driven by their empathy levels. These varying levels of empathy are likely to impact the types of music that people choose to listen to, not only in the long-term, but also in the short-term, depending on temporary fluctuations in empathy.Rentfrow and colleagues provided evidence that people's musical preferences can be organized into five robust dimensions defined as the MUSIC music-preference model (Rentfrow et al, 2011. By using musical excerpts, these researchers overcame limitations presented by genre-labels[4] with the benefit of observing the specific sonic and psychological attributes in the music that participants preferred.…”
mentioning
confidence: 99%